Sleep quality, sleeping postures, and sleeping equipment in patients with ankylosing spondylitis - Yolbas, Servet; Yildirim, Ahmet; Duzenci, Deccane; Gundogdu, Baris; Ozgen, Metin; Koca, Suleyman Serdar (Tubitak Scientific & Technological Research Council Turkey, 2017)
Background/aim: Inflammatory back pain, spinal stiffness, and limited spinal mobility are characteristic features of ankylosing spondylitis (AS). Sleeping postures can affect and/or reflect sleeping disturbances. The aim of the study was to evaluate sleeping postures and sleep disturbances in patients with AS. Materials and methods: Seventy-seven patients with AS and 49 healthy controls were enrolled. The Pittsburgh Sleep Quality Index (PSQI) and the Insomnia Severity Index (ISI) were applied to both groups. The most common sleeping postures were noted. Results: There was no significant difference between the groups in terms of sleeping postures. Total PSQI and ISI scores were higher in the AS group than in the controls (P = 0.004 and P = 0.038, respectively). The selection of sleeping postures of active and inactive patients were similar. The number of pillows used was not the same in the AS and control groups (P = 0.016). The frequency of customized bed use was higher in the AS group compared to the control group (P = 0.004). Conclusion: Sleep disturbances are more of a problem in patients with AS compared to healthy patients and in active AS patients compared to inactive ones. However, sleeping postures do not seem to affect either sleep disturbances or disease activity in patients with AS.
Keywords: Ankylosing spondylitis; sleeping postures; sleeping disturbances